Checklist of the Stink Bugs (Hemiptera: Pentatomidae) from the Caatinga region, with the description of Aridocoris guidonae gen. and sp. nov. - Miranda, Alexandre M.; López, Guilherme E. L.; Carrenho, Renan; Schwertner, Cristiano F. (Zootaxa, 2025)
Caatinga is the major natural area of the northeastern region of Brazil, covering ca. 10% of the national territory. Coupling eight sampling expeditions between 2018 and 2021 and an extensive bibliographic survey, here we present a checklist of Pentatomidae from the Caatinga comprising 53 species. In total, we collected 43 species in four federal conservation units throughout the region, while records of ten additional species were recovered from the literature. Sixteen species are recorded for the first time in the Caatinga, and one new genus and species, Aridocoris guidonae gen. and sp. nov. are described. At least 10 species (18% of the records) are only known associated with the region or with adjacent areas.